Reduction of high intensity activity during senior elite rugby league matches - Sykes, D.; Twist, C.; Lamb, K.; Nicholas, C. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
The amount of high intensity activity (HIA) performed by players has been shown to discriminate between playing standards in soccer (Mohr et al., 2003). Moreover, irrespective of playing standard, fatigue during competitive match play will manifest itself as a reduction in HIA during the final 15 min of play (Mohr et al., 2003). However, in the only study to-date investigating the changes in movement intensities in competitive rugby league (RL) matches, the researchers reported findings that were inconsistent and seemingly dependent on playing standard (Sirotic et al., 2009). Therefore, the aim of the present study was to clarify the changes in movement intensities observed during senior elite RL matches. Methods: Following ethical approval, a semi-automated match analysis image recognition system (ProZone 3, ProZone®, Leeds, England) was used to track players (n = 78) during three senior elite matches. The players` movements were classified into locomotive categories of standing: <0.2 m/s; walking: 0.2-1.9 m/s; jogging: 2.0-3.9 m/s; running: 4.0-5.4 m/s; high intensity running: 5.5-6.9 m/s and sprinting: ≥ 7 m/s (low intensity activity - LIA: 0-3.9 m/s; HIA: ≥ 4.0 m/s). The distance covered in each of the locomotive categories was calculated per half, for every 20 min of the match and for the whole match. To prevent the effects of clock stoppages, only data obtained from the first 40 min of each half was used for analyses. Results: Distances covered in running and sprinting were significantly lower in the second half in comparison to the first (P<0.05). Furthermore, mean distance covered in HIA was 14.4% lower in the second half (708 ± 146 m) than the first (827 ± 117 m; P<0.05). In addition to a reduction in HIA during 20-40, 40-60 and 60-80 min compared to 0-20 min, there was also a reduction in HIA during 60-80 min compared to 40-60 min (P<0.05). Conversely, mean total distance covered was only 1.4% (-56 m) lower in the second half due to HIA accounting for only 24.1% of the overall distance covered and a non-significant 2.0% increase in LIA in the second half (P>0.05). Discussion: The finding of this study that senior elite players exhibit an inability to maintain HIA in the second half (- 14.4%), especially toward the end of a match (60-80 min), is in-line with previous research reporting significant reductions in running and sprinting in the second half of senior elite RL matches (Sirotic et al., 2009). Furthermore, evidence from the current study suggests distance covered in HIA is more effective at detecting fatigue than total distance covered. Therefore, coaches